An exploratory review of the design literature: Gaps and avenues for future research - Beatrice D'Ippolito (The University of Manchester, Manchester Business School, 2012)
The importance of design has been recognised by scholars from different fields such as artificial sciences and engineering, innovation, arts and creativity and management. Despite a shared understanding of the role of design as a potential enabler of innovation, it still acknowledges a wide range of meanings for two main reasons: the differing motivation underpinning a design project (from purely artistic to purely engineering, problem-solving) and the types of knowledge design can rely on (e.g., rational and calculative knowledge for engineering designers; subjective and expressive knowledge for graphic designers). It appears difficult to draw boundaries within the design field and identify a criterion for a clear-cut differentiation, yet most of the available definitions seem to share three attributes: design may refer to a process, which is goal-oriented; and the set of goals consists of solving problems, improving situations, or creating something new. The paper reviews the extant design literature and contributes to it by providing a structure for a deeper understanding of design. It emphasises: (i) the passage design has undergone from as expressing certain product specifications to being an important tool that can shape firms' strategy, and (ii) the extent to which both organisational and institutional factors have contributed to this process. It concludes by identifying the gaps within the literature that deserve further attention.
Keywords: 330; Design; literature review; design science; design activity; design industry; design management; Kreativität; Produktgestaltung; Produktmanagement; Bibliometrie